Effect of Titanium Addition on the Thermal Properties of Diamond/Cu-Ti Composites Fabricated by Pressureless Liquid-Phase Sintering Technique - Chih-Yu Chung; Chao-Hung Chu; Mu-Tse Lee; Chun-Ming Lin; Su-Jien Lin (The Scientific World Journal)
In this study, minor-addition elements such as Si, Co, Cr, W, Mo, and Ti were added to matrix to improve the wettability between the diamonds and Cu matrix. The pressureless liquid-phase sintering technique adopted in this study provides a low-cost method for producing diamond/Cu composites with high potential for industrial mass production. Thermal properties of the diamond/Cu-Ti composites fabricated by pressureless liquid-phase sintering at 1373 K with variation in Ti contents were thoroughly investigated. XRD and TEM analysis show that TiC layer formed in the interface between Cu and diamond. The composites exhibited thermal conductivity as high as 620 W/m·K for 50 vol% diamond/Cu-0.6  at % Ti composite with diamond particle size of 300 µm. This value comes up to 85% of the thermal conductivity calculated by the Hasselman and Johnson (H-J) theoretical analysis. Under these conditions, a suitable coefficient of thermal expansion of 6.9 ppm/K was obtained.